2021
DOI: 10.1101/2021.08.04.21261595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural racism and COVID-19 response: Higher risk of exposure drives disparate COVID-19 deaths among Black and Hispanic/Latinx residents of Illinois, USA

Abstract: BACKGROUND: Structural racism has driven and continues to drive policies that create the social, economic, and community factors resulting in residential segregation, lack of access to adequate healthcare, and lack of employment opportunities that would allow economic mobility. This results in overall poorer population health for minoritized people. In 2020, Black and Hispanic/Latinx communities throughout the United States, including the state of Illinois, experienced disproportionately high rates of COVID-19… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Although the daily volume of sentinel samples fluctuated substantially over the study period and the sentinel population was not demographically representative of Chicago’s population at-large, R(t) estimated from sentinel cases was in good agreement with R(t) estimated from hospital data in the general population. Since the COVID-19 pandemic did not affect various racial and ethnic groups to the same extent in Illinois [17], and the sentinel population was more Hispanic/Latino than the general population, the small divergence between sentinel R(t) and hospital-based R(t) could indicate true differences in transmission dynamics between the sentinel and general populations. However, the general agreement in sentinel R(t) and hospital admissions R(t) is impressive given the biased sampling frame of the sentinel cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the daily volume of sentinel samples fluctuated substantially over the study period and the sentinel population was not demographically representative of Chicago’s population at-large, R(t) estimated from sentinel cases was in good agreement with R(t) estimated from hospital data in the general population. Since the COVID-19 pandemic did not affect various racial and ethnic groups to the same extent in Illinois [17], and the sentinel population was more Hispanic/Latino than the general population, the small divergence between sentinel R(t) and hospital-based R(t) could indicate true differences in transmission dynamics between the sentinel and general populations. However, the general agreement in sentinel R(t) and hospital admissions R(t) is impressive given the biased sampling frame of the sentinel cases.…”
Section: Discussionmentioning
confidence: 99%
“…Incident cases, the fraction of diagnostic tests that return a positive result (test positivity rate, TPR), or any other metric based on diagnostic testing in the general population is subject to bias due to fluctuating access to, availability of, and demand for diagnostic testing. These factors vary across time, geography, age, and racial and ethnic groups, and the data needed to control for these biases is often unavailable [1,[13][14][15][16][17]. The timeliness of data can also be hampered by long turn-around-times and delays in vendors' reporting of test results to health agencies [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hispanic males with age less than 8.12 had a high the chance of the infection. In addition, other studies have also reported a discordance of COVID-19 prevalence in Hispanic ethnicities [22]. It is not surprising that the top few important symptoms were gastrointestinal, fever, and congestion as literature suggests these as the common symptoms during COVID-19 infection [23].…”
Section: Plos Onementioning
confidence: 99%
“…Services for individuals with childhood-onset disability and their families required rapid shifts to remote or hybrid delivery, 1 while some families experienced a dramatic decline in access. 2 Disparities related to race that existed prior to the pandemic were magnified 3 and disabled children were disproportionately affected by school and health care disruptions. 4 The pandemic demanded reliance on online technology as our main source of connection with colleagues.…”
Section: Reflecting On the Covid-19 Pandemic And Moving Forward: Make...mentioning
confidence: 99%